Respuesta :

Answer:

1) Answer: 3)  [tex]~~x = -3 \pm \sqrt{7}[/tex]

2) Answer: 3) 2 and -6

Step-by-step explanation:

1)

[tex] (x + 3)^2 = 7 [/tex]

[tex] x + 3 = \pm \sqrt{7} [/tex]

[tex] x = -3 \pm \sqrt{7} [/tex]

Answer: [tex] 3)~~x = -3 \pm \sqrt{7} [/tex]

2)

[tex] 2(x + 2)^2 - 4 = 28 [/tex]

[tex] 2(x + 2)^2 = 32 [/tex]

[tex] (x + 2)^2 = 16 [/tex]

[tex] x + 2 = \pm \sqrt{16} [/tex]

[tex] x + 2 = \pm 4 [/tex]

[tex] x + 2 = 4 [/tex]   or   [tex] x + 2 = -4 [/tex]

[tex] x = 2 [/tex]   or   [tex] x = -6 [/tex]

Answer: x = 2 or x = -6

Answer:

1) Answer: 3)  ~~x = -3 \pm \sqrt{7}

2) Answer: 3) 2 and -6

Step-by-step explanation:

ACCESS MORE